DEVELOPMENT OF SOFTWARE PRODUCT TO SUPPORT THE PROCESS OF INTERNAL AUDIT OF A FOOD COMPANY - Ermolaeva E.O.; Trofimova N.B.; Trofimov I.E. (Техника и технология пищевых производств)
In the process of organizing food production, there is a constant need to control the quality and safety of products, control technological and organizational and managerial processes. The solution of this task is the internal audit of the integrated management system that operates at the enterprise, which allows identifying and timely eliminating inconsistencies. When carrying out internal checks, a large amount of data is generated about the operation of the enterprise, including positive and negative observations, information on identified observations, analysis of causes of inconsistencies, corrective and preventive actions. With the current level of information technology development, organizations can optimize the process of data collecting, accounting and analyzing. The proposed software product is designed to ensure the passage of audit within the organization, using a systematic approach to evaluate and improve the efficiency of processes through the use of computer technology and statistical methods. To develop the program the requirements of the standards for management systems and audit have been analyzed; classification of inconsistencies and statistical data on the elimination of comments at the enterprise has been applied. Based on the obtained data a program has been developed in the Microsoft Visual Studio 2010 for data processing and generating automated reports for the selected period. The result of the research is the development of recommendations "Audit of an integrated management system" for optimizing the process by the example ofconfectionery production. Forms for accounting inconsistencies, containing data on inconsistencies, its classification in terms of significance, in terms of ensuring the safety of manufactured products, planned corrective actions, as well as the form of notification of deadlines for remedial measures have been developed. The "Analysis of audit data" sub-process has been automated. To approbate the software product a list of inconsistencies based on the results of external and internal audits for 2016 has been designed and ranked.